Sporendocladia bactrospora associated with wounds on native broadleaved trees in Norway and Sweden. Issue 2 (10th October 2013) - Roux, J.; Solheim, H.; Kamgan Nkuekam, G.; Wingfield, M. J.; Sturrock, R.
Summary A survey to identify ophiostomatoid fungi that infect wounds on native Norwegian and Swedish broadleaved trees was undertaken during summer 2004. A fungus resembling a species of Sporendocladia was commonly isolated from the exposed cambium and inner bark of wounds. Morphological examination and comparisons of DNA sequence data for the ITS and 5.8S regions of the rRNA gene region led to its identification as Sporendocladia bactrospora. Pathogenicity trials on young Populus tremula and Betula pubescens trees showed that S. bactrospora is capable of causing lesions on these trees. There have been few previous reports of S. bactrospora, and in most cases, these have been as saprophytes on wood. In contrast, results of this study show that it is a common inhabitant of freshly made wounds on native broadleaved trees in Scandinavia, and it appears to contribute to staining of wood.